Actitudes y conocimiento sobre la donación y trasplante de órganos en usuarios del Centro de Salud Universitario de Motupe - León Salinas, Karina Michelle (2023)
Organ transplantation can sometimes be the only alternative for many patients to survive or improve their life quality, therefore, the purpose of this research was to apply the modified questionnaire PCID DTO RIOS (Donor International Collaborative Project on organ donation and transplantation developed by Ríos), with the objective of determining the attitudes and knowledge about organ donation and transplantation, identifying the predisposition to be donors according to age and sex of the users in the period August 2021 - January 2022. It had a prospective and cross-sectional approach, with a sample of 323 participants from the University Health Center of Motupe, obtaining a prevalence of predisposition to donate in female users aged 18-24 years with 15.2% (n=49), 62.23% (n=201) did not express concern that their body would be scarred after organ donation. Of the reasons in favor, 37.77% (n=122) were for solidarity and 16.41% (n=53) were for fear that organs would be removed before death. A total of 76.16% (n=246) of the users were aware of the concept of brain death and 50.46% (n=163) considered that they had an adequate level of information on organ donation and transplantation. It is concluded that the decision to donate is based on knowledge about this topic, therefore the sociocultural environment influences the disposition and attitude towards being a donor or not